Statin Use in COVID-19 Hospitalized Patients and Outcomes: A Retrospective Study - Kouhpeikar, Hamideh; Khosaravizade Tabasi, Hamidreza; Khazir, Zahra; Naghipour, Armin; Mohammadi Moghadam, Hussein; Forouzanfar, Hasan; Abbasifard, Mitra; Kirichenko, Tatiana V.; Reiner, Željko; Banach, Maciej; Sahebkar, Amirhossein (Frontiers in Cardiovascular Medicine, 2022)
Background Coronavirus disease 2019 (COVID-19) might affect everyone, but people with comorbidities such as hypertension and cardiovascular disease (CVD) may often have more severe complications and worse outcomes. Although vaccinations are being performed worldwide, it will take a long time until the entire population of the world is vaccinated. On the other hand, we are witnessing the emergence of new variants of this virus. Therefore, effective therapeutic approaches still need to be considered. Statins are well-known lipid-lowering drugs, but they have also anti-inflammatory and immunomodulatory effects. This study aimed to investigate the effects of statins on the survival of COVID-19 hospitalized patients. Methods This retrospective study was performed on 583 patients admitted to a highly referenced hospital in Tabas, Iran, between February 2020 and December 2020. One hundred sixty-two patients were treated with statins and 421 patients were not. Demographic information, clinical signs, and the results of laboratory, and comorbidities were extracted from patients' medical records and mortality and survival rates were assessed in these two groups. Results The results of the Cox crude regression model showed that statins reduced mortality in COVID-19 patients (HR = 0.56, 95% CI: 0.32, 0.97; p = 0.040), although this reduction was not significant in the adjusted model (HRs=0.51, 95%CI: 0.22, 1.17; p = 0.114). Using a composite outcome comprising intubation, ICU admission, and mortality, both crude (HR = 0.43; 95% CI: 0.26, 0.73; p = 0.002) and adjusted (HR = 0.57; 95% CI: 0.33, 0.99; p = 0.048) models suggested a significant protective effect of statin therapy. Conclusion Due to anti-inflammatory properties of statins, these drugs can be effective as an adjunct therapy in the treatment of COVID-19 patients.